2008
DOI: 10.1523/jneurosci.3476-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Interactions between the Ventral Visual Stream and Emotion-Related Structures Rely on a Two-Pathway Architecture

Abstract: Visual attention can be driven by the affective significance of visual stimuli before full-fledged processing of the stimuli. Two kinds of models have been proposed to explain this phenomenon: models involving sequential processing along the ventral visual stream, with secondary feedback from emotion-related structures ("two-stage models"); and models including additional short-cut pathways directly reaching the emotion-related structures ("two-pathway models"). We tested which type of model would best predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
118
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(137 citation statements)
references
References 56 publications
17
118
1
Order By: Relevance
“…It should be noted that the late latency response we report is in contrast to early emotion-evoked neuromagnetic activity observed in ventral extrastriate cortex (Rudrauf et al, 2008) beginning from 0.1 s poststimulus onset. We do, however, observe, at the sensor level an emotional modulation of the ERFs before the onset of mLPP time window at 0.2-0.4 s (Fig.…”
Section: Discussioncontrasting
confidence: 95%
“…It should be noted that the late latency response we report is in contrast to early emotion-evoked neuromagnetic activity observed in ventral extrastriate cortex (Rudrauf et al, 2008) beginning from 0.1 s poststimulus onset. We do, however, observe, at the sensor level an emotional modulation of the ERFs before the onset of mLPP time window at 0.2-0.4 s (Fig.…”
Section: Discussioncontrasting
confidence: 95%
“…Some techniques might improve these investigations, as shown by a recent fMRI study using a fast slice acquisition protocol (Sabatinelli, et al, 2009) that confirmed a sequential two-stage activation from amygdala to fusiform cortex. Thus, this study could show that a differential emotional discrimination arose in the amygdala approximately 1 s before extrastriate occipital cortex (no differential effect was found in the striate cortex), consistent with a re-entrant organization of emotional inputs along visual pathways (Vuilleumier, 2005;Rudrauf, et al, 2008;Sabatinelli, et al, 2009). However, this timing difference is relatively long and somewhat hard to reconcile with responses latencies observed with other techniques (single neuron firing rate, EEG or MEG), and even fast fMRI might not have sufficient temporal resolution to establish a precise timing of information transmission.…”
Section: Box Contentssupporting
confidence: 79%
“…In addition, recent DTI data in humans suggest that early occipital areas may project to anterior temporal lobe (including amygdala) through direct white-matter fibers in the inferior longitudinal fasciculus (Catani, et al, 2003;Gschwind, et al, in press). Moreover, MEG recordings and connectivity models of brain responses to visual emotional stimuli suggest that the latency and distribution of activity in occipitotemporal regions is best accounted for by a functional architecture involving both rapid inputs through a short-cut to the amygdala and subsequent feedback from amygdala to early cortical areas, rather than by a strictly sequential processing along the ventral visual stream (Rudrauf, et al, 2008). These results support a dual route hypothesis, but a subcortical route or cortico-cortical long-range pathways appear equally plausible, and the exact anatomical substrates of these effects therefore remain to be clarified.…”
Section: Neural Routes To the Amygdalamentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers argue for a subcortical route by which low spatial frequency visual information about objects and faces can bypass V1 via the amygdala to represent affective value in the body and behaviour (e.g. LeDoux 1996LeDoux , 2000Weiskrantz 1996;Morris et al 1998;Catani et al 2003;Rudrauf et al 2008), whereas others argue that such a circuit is not functional in primates (Rolls 2000;Pessoa & Ungerleider 2004). Either way, affective predictions do not necessarily require a purely subcortical route.…”
Section: Coordinating Affective Predictions In the Brainmentioning
confidence: 99%